TINJAUAN YURIDIS KEWENANGAN PENGADILAN NIAGA DALAM MENGADILI PERKARA KEPAILITAN YANG DIDALAMNYA TERDAPAT KLAUSULA ARBITRASE - Cahyani, Metya Mutiara; Yunani, Ailly Latiefah (Wacana Hukum, 2023)
Social conflicts are common. Every aspect of life—business, family, politics, and the economy—can have issues. Conflicts, disagreements, and fear of damage often trigger these issues. Current dispute settlement solutions go beyond court. The parties can agree on a dispute resolution. All disputes can be settled outside of court. Arbitration resolves disputes. Arbitration is a technique to resolve a civil dispute outside of court based on a written arbitration agreement (Article 1 point 1 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution). This paper examines the Commercial Court's jurisdiction in bankruptcy cases with an arbitration provision. This solution applies legal norms to the situation. General legal and statutory theories are analyzed descriptively. According to the research, the Commercial Court's authority extends beyond bankruptcy cases and postponement of debt obligations and payments (PKPU). Article 303 of the KPKPU Law confirms that the court can examine and resolve parties' bankruptcy statements even if their debt agreement contains an arbitration clause. The arbitration provision does not preclude bankruptcy legislation. If Article 2 paragraph (1) jo. Article 8 paragraph (4) of the KPKPU Law is met, a bankruptcy application can be submitted.